Critical Materials in Automotive Industry: A Brief Review - Richert, Maria; Łebkowski, Piotr; Kulczycka, Joanna; Iwaszczuk, Natalia (European Journal of Applied Sciences, 2023)
Metals in the automotive industry are the basis of production. Due to the transformation of the automotive industry towards electromobility, the demand for materials defined as critical is increasing. Critical materials include, among others: iridium (Ir), cobalt (Co), neodymium (Nd), dysprosium (Dy), gallium (Ga), terbium (Tb), graphite and platinum (Pt). The article characterizes critical materials, with particular attention paid to rare earth metals, without which the production of modern cars would be impossible. Obtaining this group of materials is associated with supply problems, lack of diversification of supplies and unclear impact of their production technology on the environment, due to the location of the industry in poorly controlled regions where compliance with ecological principles is questionable. The article is a review of data taken from studies, reports and articles regarding critical materials in the automotive industry. It addresses the most important problems related to the extraction and production of this group of metals, prices, the impact of their production on the environment and their use in cars.